Life Cycle Assessment of Building Renovation Measures–Trade-off between Building Materials and Energy - Ricardo Ramírez-Villegas (Energies, 2019)
The scope of this study is to assess how different energy efficient renovation strategies affect the environmental impacts of a multi-family house in a Nordic climate within district heating systems. The European Union has set ambitious targets to reduce energy use and greenhouse gas emissions by the year 2030. There is special attention on reducing the life cycle emissions in the buildings sector. However, the focus has often been on new buildings, although existing buildings represent great potential within the building stock in Europe. In this study, four different renovation scenarios were analyzed with the commercially available life cycle assessment software that follows the European Committee for Standardization (CEN) standard. This study covers all life cycle steps from the cradle to the grave for a residential building in Borlänge, Sweden, where renewable energy dominates. The four scenarios included reduced indoor temperature, improved thermal properties of building material components and heat recovery for the ventilation system. One finding is that changing installations gives an environmental impact comparable to renovations that include both ventilation and building facilities. In addition, the life cycle steps that have the greatest environmental impact in all scenarios are the operational energy use and the building and installation processes. Renovation measures had a major impact on energy use due to the cold climate and low solar irradiation in the heating season. An interesting aspect, however, is that the building materials and the construction processes gave a significant amount of environmental impact.